Strengthening for Self-Efficacy and Parenting Patterns in Improving Online Learning Outcomes of Elementary School Students During the Covid-19 - Anggraeni, Imas; Sumirat, Fanny (Global Writing Academica Researching & Publishing, 2025)
The article aims to analyze and describe the strengthening of self-efficacy and parenting patterns on Elementary school students' learning outcomes during online learning. The success of students' academic achievement cannot be separated from parents' contribution and involvement directly in accompanying their children to study online at home. The method used is a systematic literature review (SLR) by collecting informative data by identifying, evaluating, and examining all research topics. The research result shows that self-efficacy and involvement of parenting patterns contributed significantly to improving the learning outcome of Elementary school students. The contribution of this study is to develop a parenting program that can support students' learning success at home during online learning in the Covid-19 pandemic.